FAMILY SCIOMYZIDAE - Marinoni, Luciane; Murphy, William L. (Zootaxa, 2016)
The Sciomyzidae are a family of acalyptrate flies of worldwide distribution, with 543 extant species and 14 described subspecies in 63 genera. Although 274 species in 37 genera are found in the Western Hemisphere, the sciomyzid fauna of Central and South America remains relatively unknown, comprising 103 species in 25 genera, with only seven species in five genera having been recorded from Colombia: Dictya bergi Valley, Perilimnia albifacies Becker, Pherbellia guttata (Coquillett), Sepedomerus bipuncticeps (Malloch), S. macropus (Walker), Sepedonea guianica (Steyskal), and S. isthmi (Steyskal).